Effects of size and thermophilic pre-hydrolysis of banana peel during anaerobic digestion, and biomethanation potential of key tropical fruit wastes. (October 2017) - Odedina, Mary Jesuyemi; Charnnok, Boonya; Saritpongteeraka, Kanyarat; Chaiprapat, Sumate
Graphical abstract: Highlights: Digestibility of tropical fruit wastes is in order of banana, longan and rambutan. Size reduction increased CH4 yield of LF banana peel by 23.2% in batch assay. H2 and CH4 were produced by adding the front-end thermo pre-hydrolysis tank. Thermo pre-hydrolysis tank provided methanogenic system stability at high solid feed. Two stage digestion gave higher VS destruction and energy yield at high solid feed. Abstract: Methane production potential of tropical fruit wastes, namely lady-finger banana peel, rambutan waste and longan waste were compared using BMP assay and stoichiometric modified Buswell and Mueller equation. Methane yields based on volatile solid (VS) were in the order of ground banana peel, chopped banana peel, chopped longan waste, and chopped rambutan waste (330.6, 268.3, 234.6 and 193.2 mLCH4 /gVS) that corresponded to their calculated biodegradability. In continuous operations of banana peel digestion at feed concentrations based on total solid (TS) 1–2%, mesophilic single stage digester run at 20-day hydraulic retention time (20-day HRT) failed at 2%TS, but successfully recovered at 1.5%TS. Pre-hydrolysis thermophilic reactor (4-d HRT) was placed as pre-treatment to mesophilic reactor (20-d HRT). Higher biogas (with an evolution of H2 ) and energy yields were obtained and greater system stability was achieved over the single stage digestion, particularly at higher solid feedstock. The best performance of two stage digestion was 68.5% VS destruction and energy yield of 2510.9 kJ/kgVS added at a feed concentration of 2%TS.